Intuitive eating and food intake in men and women: Results from the Swiss food panel study. (1st April 2019) - Horwath, Caroline; Hagmann, Désirée; Hartmann, Christina
Abstract: Although intuitive eating (IE) interventions have consistently shown benefits for psychological wellbeing and some have shown improvements in physical wellbeing, there is scarce information on the relationship between IE and food intake. Given the popularity of IE as an alternative to dieting, it's important to explore its relationship with food intake. The relationships between IE, Body Mass Index (BMI), diet quality, self-evaluation of dietary intake and physical activity were investigated. A randomly selected sample of adults from the German and French-speaking parts of Switzerland ( N  = 5, 238, 51% men, 20–100 years, BMI 15–62 kg/m 2 ) completed a self-administered questionnaire comprising measures of a diverse range of eating related variables. Intuitive Eating was assessed with the IES-2. Food intake was measured with a semiquantitative food frequency questionnaire. Pearson correlations between the IES-2 and variables of interest were calculated for men and women separately. Although total IES-2 scores showed moderate negative correlations with BMI in men and women, the four IES-2 subscales showed different relationships with food intake. In contrast to the other subscales, unconditional permission to eat moderately correlated with poorer diet quality scores, and consistently showed associations with a more negative self-evaluation of eating behavior. The other three IES-2 subscales showed a few small positive and negative correlations with food intake, including small positive associations of diet quality scores in women, but not men, with eating for physical rather than emotional reasons and reliance on hunger and satiety cues. Further studies are needed to determine the impact of IE interventions on food intake.